PERENCANAAN KARIR MAHASISWA PENDIDIKAN TEKNIK MESIN DI UNIVERSITAS SRIWIJAYA - Ramadinah, Nadya; Tastiara, Tastiara; Febiolantika, Saniya Putri Ayu; Wahdania, Wahdania; Madira, Juwita; Alrefi, Alrefi (Universitas Muria Kudus, 2025)
One of the essential elements in a student's life is career planning. Students must prepare themselves to compete and adapt to market demands in an era filled with global competition and rapid changes in the world of work. Good career planning helps students identify their interests, talents, and long-term goals. This research was conducted by deeply exploring the experiences, views, and perceptions of individuals regarding their careers. In this study, a qualitative research method with a qualitative descriptive approach was used. Data was collected from interviews with three Mechanical Engineering Education students at Sriwijaya University. The results of this study indicate that all three valued internship experiences and higher education in helping them prepare for their careers. They have different challenges and strategies in facing academic demands, but they all emphasize the importance of enthusiasm, effort, and time management.